2011
DOI: 10.1097/rhu.0b013e31821c020a
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Predictors of Kidney Disease Progression in Puerto Ricans With Systemic Lupus Erythematosus Initially Presenting With Mild Renal Involvement

Abstract: Objectives The aims of this study were to determine the outcome and predictors of renal disease progression in Puerto Ricans with systemic lupus erythematosus (SLE) initially presenting mild renal involvement. Methods A retrospective cohort of 61 SLE patients (per American College of Rheumatology classification) with mild renal involvement was studied. Mild renal disease was defined as glomerular filtration rate (GFR) ≥ 90 ml/min in the presence of proteinuria (> 0.25g/day, but < 3.5 g/day), hematuria, and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In our study we showed that normal complement levels were associated with a higher probability of achieving complete recovery in proteinuria as compared to low complement levels. Nieves-Plaza, et al, showed that low C4 levels were predictors of an earlier decline in renal function as determined by GFR 14 . Further, our analysis showed that males had lower probability of achieving complete remission of proteinuria than female patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we showed that normal complement levels were associated with a higher probability of achieving complete recovery in proteinuria as compared to low complement levels. Nieves-Plaza, et al, showed that low C4 levels were predictors of an earlier decline in renal function as determined by GFR 14 . Further, our analysis showed that males had lower probability of achieving complete remission of proteinuria than female patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are racial differences in the renal outcomes of patients with LN. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . However, few studies on the long-term renal outcomes of Chinese patients have been reported, all of which were derived from small patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Various prognostic factors have been reported in patients with LN in western countries, such as ethnicity, age at LN onset, gender, unfavourable histological features, increased levels of serum creatinine, anti-double-stranded DNA antibodies (anti-dsDNA), a low level of C 4 , poor socioeconomic status and psychosocial factors. [6][7][8][9][10][11][12] These results showed that predictors associated with poor outcome in LN varied with different cohorts, making it difficult to extrapolate findings from one centre to another, even in the same geographic region. In China, which accounted for 19% of the world's population, the LN cumulative incidence was higher than other populations.…”
Section: Introductionmentioning
confidence: 99%